Kardiomiopati Peripartum sebagai Penyebab Stroke pada Usia Muda - Abirawa, Leon; Victory, Viky; Kamil, Muhammad Firdaus (Cermin Dunia Kedokteran, 2024)
Peripartum cardiomyopathy can be a cause of stroke in the younger population. A case of stroke in a young woman caused by peripartum cardiomyopathy with early presentation mimics pulmonary tuberculosis is presented. This is a cause for concern in countries with a high prevalence of TB infection.